Preparation of Polyester/ Micro Eggshell Fillers Composite as Natural Surface Coating - Jassim, Aveen N.; Jassim, Widad H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
To fabricate an inexpensive surface coating with excellent mechanical properties with good water resistance and thermal diffusion, white eggshell fibers with particle size (~1micrometer) has been added by different weight percentages (1,2,3,4,5,6,7 and 8 %) to Unsaturated Polyester.The weight ratio (4%) of eggshell powder is a good ratio to be added to polyester to improve its mechanical properties, such as hardness, impact strength, and wear resistance. The hardness was improved by (3.75%); impact strength has the same value as polyester, flexural strength by (8.43%) and high improvement in wear resistance (74.4%), as well as to get further improvements in mechanical properties of polyester, the eggshell powder was added with (5%), where the hardness was improved by (3.63%), impact strength improved by (~23%) and the flexural strength by (23.23%)but the wear resistance by (2.15%) only .The resistance to thermal of polyester was improved to (9.95%) and (13.77%) by adding the eggshell powder with ratios (of 4%) and (5%), respectively.(Polyester/ 4% eggshells).  And (Polyester/ 5% eggshells) composites have a higher resistance to water diffusion after being immersed in water between (1-4 weeks).The electron microscope image was used to observe the degree of homogeneity in polyester composite microstructure, which improved the results mechanical and thermal results.